2010
DOI: 10.1128/iai.00359-10
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Malaria GlycosylphosphatidylinositolIn Vitroby Serum IgG from Malaria-Exposed Individuals

Abstract: Parasite-derived glycosylphosphatidylinositol (GPI) is believed to be a major inducer of the pathways leading to pathology and morbidity during Plasmodium falciparum infection and has been termed a malaria "toxin." The generation of neutralizing anti-GPI ("antitoxic") antibodies has therefore been hypothesized to be an important step in the acquisition of antidisease immunity to malaria; however, to date the GPI-neutralizing capacity of antibodies induced during natural Plasmodium falciparum infection has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…GPI has been proposed as a putative malaria toxin eliciting the inflammatory response contributing to pathogenesis [12]. On one hand, GPIs initiate the release of proinflammatory cytokines including TNF-a, IL-1, and IL-6, on the other hand antibodies against GPI mediate an inhibition of cytokines release as demonstrated in vitro [34]. However, no correlation was detected in the present work between anti-GPI IgG levels and plasmatic concentrations of proinflammatory cytokines, TNF-a, and IL-6, during the three days survey.…”
Section: Immune Responses To Malarial Gpismentioning
confidence: 99%
“…GPI has been proposed as a putative malaria toxin eliciting the inflammatory response contributing to pathogenesis [12]. On one hand, GPIs initiate the release of proinflammatory cytokines including TNF-a, IL-1, and IL-6, on the other hand antibodies against GPI mediate an inhibition of cytokines release as demonstrated in vitro [34]. However, no correlation was detected in the present work between anti-GPI IgG levels and plasmatic concentrations of proinflammatory cytokines, TNF-a, and IL-6, during the three days survey.…”
Section: Immune Responses To Malarial Gpismentioning
confidence: 99%
“…This is still up for debate, since studies that find an association between PfGPI-specific antibody titer and protection from severe malaria (Brasseur et al, 1990 ; Naik et al, 2000 ; Gowda, 2002 ; Keenihan et al, 2003 ; Perraut et al, 2005 ) are balanced by studies that find no such association (de Souza et al, 2002 ; Boutlis et al, 2005 ; Cissoko et al, 2006 ; Gomes et al, 2013 ; Mbengue et al, 2016 ). However, PfGPI-specific antibodies are reported to show relevant action in modulating immune responses by protecting immune cells against severe P. falciparum- induced inflammatory responses in-vitro (Schofield et al, 1993 ; de Souza et al, 2010 ).…”
Section: Exploiting Carbohydrate Antigens For Protozoan Parasite Vaccmentioning
confidence: 99%
“…GPI anchors can activate macrophages and cells of the vascular endothelium through several signalling pathways that result in the production of chemical mediators, such as NO, tumour necrosis factor (TNF α ) and intracellular adhesion molecules I (ICAM-I). This observation led tp exploration of this molecule as a vaccine target (Schofield et al ., 2002), a concept later reinforced by a study that demonstrated that presence of specific antibodies to P. falciparum GPI could neutralize the strong inflammatory response that GPI stimulates (de Souza et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%